Communication Behaviour of Women Vegetable Growers of Nainital District of Uttarakhand - Deepika Verma, (Indian Journal of Extension Education, 2016)
The research study was undertaken to find out information processing behaviour and approaches used by the womenvegetable growers in the six villages of Community Development Blocks, Haldwani, Ramnagar and Dhari in Nainitaldistrict of Uttarakhand. Data were collected through pre-tested semi- structured interview schedule and Focous GroupDiscussions from 150 women vegetable growers. The findings of the study revealed that the personal cosmopolitesources, which are part of farming community, live with the farmers, aware of farmers' problems, provide newtechnologies, and having close supervision, can play significant role for bringing agricultural development in the region.